2021
DOI: 10.1021/acs.jafc.1c01140
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phenolic Compounds and Hormone Accumulation Patterns between Early- and Mid-Maturing Sweet Cherry (Prunus avium L.) Cultivars during Fruit Development and Ripening

Abstract: Color acquisition is one of the most distinctive features of fruit development and ripening processes. The color red is closely related to the accumulation of polyphenolic compounds, mainly anthocyanins, during sweet cherry fruit maturity. In nonclimacteric fruit species like sweet cherry, the maturity process is mainly controlled by the phytohormone abscisic acid (ABA), though other hormones may also play a role. However, the coordinated stage-specific production of polyphenolic compounds and their relation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(149 reference statements)
3
11
0
Order By: Relevance
“…For Drunk Incense, the skin color of grapes on the same bunch is relatively similar throughout the growth process, and the judgment error mainly occurs between Mc values of 0.8 and 0.9 [ 38 ]. For example, Ponce et al [ 39 ] also found that due to the different cherry fruit varieties, differences in the accumulation of anthocyanins during the fruit development process led to potential differences in fruit evolution, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…For Drunk Incense, the skin color of grapes on the same bunch is relatively similar throughout the growth process, and the judgment error mainly occurs between Mc values of 0.8 and 0.9 [ 38 ]. For example, Ponce et al [ 39 ] also found that due to the different cherry fruit varieties, differences in the accumulation of anthocyanins during the fruit development process led to potential differences in fruit evolution, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, this difference between IAD results and the CTIFL color chart is most likely due to differential levels of compounds other than the anthocyanins. Recently we have reported a difference in the phenolic accumulation dynamics between non-anthocyanin phenols and anthocyanins during sweet cherry fruit development in these two cultivars [33].…”
Section: Cultivar Dependent Effect Of Aba Canopy Spraying Of Sweet Cherry Trees On Fruit Quality Parametersmentioning
confidence: 91%
“…In sweet cherry, though, a small respiratory peak occurs from the de-greening to the pink color initiation stage (Zhao et al, 2013). Variations in compounds that characterize sweet cherry fruits are the decrease in some phenolics and flavonols during development; and the increase in the anthocyanin concentration at the pink or red stages (Teribia et al, 2016; Ponce et al, 2021). This increase occurs simultaneously or soon after ABA accumulation (Ponce et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in compounds that characterize sweet cherry fruits are the decrease in some phenolics and flavonols during development; and the increase in the anthocyanin concentration at the pink or red stages (Teribia et al, 2016; Ponce et al, 2021). This increase occurs simultaneously or soon after ABA accumulation (Ponce et al, 2021). However, there is a cultivar-dependent increase in IAA and GA 4 (Ponce et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation